1992
DOI: 10.1016/s0095-5108(18)30465-2
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Previa

Abstract: Placenta previa occurs in approximately one in 200 pregnancies. The cause is unknown, but endometrial damage due to prior pregnancy, cesarean section, and other factors predispose to it. Diagnosis is usually made by transabdominal ultrasonography. False-positive diagnoses are common in the second trimester and the term "potential placenta previa" has been proposed to describe this situation. Bleeding with placenta previa is usually associated with uterine contractions, thus the introduction of tocolysis. Place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
1
16
0
3
Order By: Relevance
“…The observed incidence of placenta praevia of 0.4% in our study is in keeping with current literature 1,2 , and our data objectively confirm the perception that the clinical course of women with a placenta praevia is unpredictable. The degree of praevia was not predictive of the likelihood of bleeding which, while contrary to common opinion 6 , supports previous findings 10 . There were no features specific to those women who were delivered within 12 h of bleeding onset that would have predicted their need for emergency delivery.…”
Section: Discussionsupporting
confidence: 78%
“…The observed incidence of placenta praevia of 0.4% in our study is in keeping with current literature 1,2 , and our data objectively confirm the perception that the clinical course of women with a placenta praevia is unpredictable. The degree of praevia was not predictive of the likelihood of bleeding which, while contrary to common opinion 6 , supports previous findings 10 . There were no features specific to those women who were delivered within 12 h of bleeding onset that would have predicted their need for emergency delivery.…”
Section: Discussionsupporting
confidence: 78%
“…This placental migration is due to the fact that the lower segment grows faster than the placenta, and the net result of this differential growth rate is that the lower placental edge appears to move away from the internal cervical os. 1,14,17,18 While some studies have claimed that the type and degree of placenta previa may indicate the type of delivery and clinical outcome, 13,15,1 other studies have shown that the degree of placenta previa is not predictive of clinical outcomes. 4,14,20 Our study shows that the implantation site (whether anterior or posterior), the distance of the lower placental margin from the internal cervical os, and the relationship between the presenting part and the placental margin are important sonographic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Cette crainte est d'autant plus justifiée que le diagnostic de placenta praevia recouvrant est souvent mé-connu jusque tard au cours de la grossesse. C'est l'introduction du doigt dans le canal cervical qui va faire prendre un risque de saignement [34]. Le TV peut être avantageusement remplacé par l'échographie tant en terme d'information apportée qu'en terme d'innocuité.…”
Section: Un Risque De Saignement En Cas De Tv Sur Placenta Praeviaunclassified